HUBUNGAN INISIASI MENYUSU DINI DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS MERGANGSAN YOGYAKARTA - Evi Nuryuliyani; Endah Puji Astuti; Ari Sulistyawati (MEDIA ILMU KESEHATAN, 2015)
Background: Infant Mortality Rate (IMR) is one important indicator in determining the level of public health. Early breastfeeding initiation can save the lives of infants under 28 days of age. Furthermore, infants who were given the opportunity for early breastfeeding were eight times more successful to breast-fed exclusively. Early breastfeeding initiation is a process that allows the babies to find and suckle the milk by themself, within the first hour in their early life. Exclusive breastfeeding is breastfeeding without any additional food in infants until the age of six months old. Objective: This study aimed to determine the relationship between early breastfeeding initiation and exclusive breastfeeding in Mergangsan Health Center. Methods: This research was an analytic survey with a case-control design. Samples were taken by purposive sampling technique, consisted of 64 respondents. Result: Most of the mothers in Mergangsan Health Center had implemented early breastfeeding initiation (65.6%), while exclusive breastfeeding in Mergangsan Health Center was largely applied (64.1%). The chi square test revealed p=0,000 (p< 0.05) with a contingency value of 0.605. Conclusion: There was a significant relationship between early breastfeeding initiation and exclusive breastfeeding in Mergangsan Health Center. Mothers who initiated early breastfeeding were tend to be more successful in implementing exclusive breastfeeding. It is recommended for health workers to provide early breastfeeding initiation at the time of delivery as well as to motivate mothers in order to implement exclusive breastfeeding. Keywords: Early breastfeeding initiation, exclusive breastfeeding